Analisis Nilai Tambah Produk Sirup Parijoto di CV Seleksi Alam Muria Kabupaten Kudus - Puspa Indah Fitritama; Titik Ekowati; Hery Setiyawan (Universitas Galuh, 2026)
Parijoto is a local plant native to the slopes of Mount Muria with significant potential to be developed into value-added processed products, particularly in the form of syrup. This study aims to analyze the added value and profitability of parijoto syrup production at CV Seleksi Alam Muria, Kudus Regency. The scope of the research includes production processes, cost structure, revenue, income, added value, and business profitability. A descriptive quantitative method was applied using primary and secondary data collected through observation, interviews, and documentation. Added value analysis was conducted using the Hayami method, while profitability was measured by comparing net income to total production costs. The results indicate that processing parijoto fruit into syrup generates an added value of Rp 90,000 per kilogram of raw material with an added value ratio of 50%, categorized as high. However, the average profitability of 3.013% is still lower than the BRI deposit interest rate in August 2025 of 3.50%, indicating that business profitability has not yet reached an optimal level. This condition is influenced by high production costs, fluctuations in production volume, and unstable sales. Therefore, improving cost efficiency, stabilizing raw material supply, and optimizing production capacity are necessary to enhance business performance and sustainability..